Genomic features of Helicobacter pylori‐naïve diffuse‐type gastric cancer. Issue 3 (16th September 2022) - Namikawa, Ken; Tanaka, Norio; Ota, Yuki; Takamatsu, Manabu; Kosugi, Mayuko; Tokai, Yoshitaka; Yoshimizu, Shoichi; Horiuchi, Yusuke; Ishiyama, Akiyoshi; Yoshio, Toshiyuki; Hirasawa, Toshiaki; Amino, Sayuri; et al.
Abstract: Helicobacter pylori (HP) is a major etiologic driver of diffuse‐type gastric cancer (DGC). However, improvements in hygiene have led to an increase in the prevalence of HP‐naïve DGC; that is, DGC that occurs independent of HP. Although multiple genomic cohort studies for gastric cancer have been conducted, including studies for DGC, distinctive genomic differences between HP‐exposed and HP‐naïve DGC remain largely unknown. Here, we employed exome and RNA sequencing with immunohistochemical analyses to perform binary comparisons between 36 HP‐exposed and 27 HP‐naïve DGCs from sporadic, early‐stage, and intramucosal or submucosal tumor samples. Among the samples, 33 HP‐exposed and 17 HP‐naïve samples had been preserved as fresh‐frozen samples. HP infection status was determined using stringent criteria. HP‐exposed DGCs exhibited an increased single nucleotide variant burden (HP‐exposed DGCs; 1.97 [0.48–7.19] and HP‐naïve DGCs; 1.09 [0.38–3.68] per megabase; p = 0.0003) and a higher prevalence of chromosome arm‐level aneuploidies ( p < 0.0001). CDH1 was mutated at similar frequencies in both groups, whereas the RHOA–ARHGAP pathway misregulation was exclusive to HP‐exposed DGCs ( p = 0.0167). HP‐exposed DGCs showed gains in chromosome arms 8p/8q ( p < 0.0001), 7p ( p = 0.0035), and 7q ( p = 0.0354), and losses in 16q ( p = 0.0167). Immunohistochemical analyses revealed a higher expression of intestinal markers such as CD10 ( p < 0.0001) and CDX2 ( p = 0.0002) and a lower expression of the gastric marker, MUC5AC ( p = 0.0305) among HP‐exposed DGCs. HP‐naïve DGCs, on the other hand, had a purely gastric marker phenotype. This work reveals that HP‐naïve and HP‐exposed DGCs develop along different molecular pathways, which provide a basis for early detection strategies in high incidence settings. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.